Effect of abutment width on scour hole characteristics around abutment in compound channel - Lian, Lian (2017)
Scouring is one of the most critical outcome of flow around bridge structure and it is mainly responsible for the failure of bridge foundations. Therefore, it is important to be able to estimate the accurate maximum depth of scouring to design a safe and economical depth of bridge footing. This study investigates the effect of width of 〖45〗^owing wall abutment and time on scour hole characteristics and maximum scour depth. A series of experiments were conducted in a 19m long and 1.6m wide 2 staged compound channel. The sand property, flow intensity and abutment length were kept constant. The results of 3 groups of experiments were represented (2 experiments per group) covering 6 possible combinations of varying abutment width, flow rate and flow depth ratio. A point gauge was used to measure the bathymetry of scour hole, the length and width of scour hole were also measured at different time intervals and, finally, the volume of scour hole was measured at the equilibrium stage of experiment. Thereafter, time development curves and scour profiles were established to determine equilibrium time, equilibrium scour depth and scour hole geometry. The relationship between variables and scour hole geometries were demonstrated using dimensional analysis. Results show that abutment width has an influence on geometric variables of the scour pattern such as the maximum scour depth, length and volume of scour hole. Furthermore, the effect of increasing abutment width on scour length and volume is much greater than on scour depth.